Perfil de susceptibilidade antimicrobiana in vitro de Klebsiella pneumoniae isoladas de animais domésticos e silvestres - Ito, Alessandra Tammy Hayakawa (2018)
Klebsiella pneumoniae (K. pneumoniae) is an opportunistic pathogen responsible for several types of nosocomial infections and is considered a multiresistant microorganism. Data in the literature that provide information regarding the resistance of this microorganism to antimicrobials in animal samples are scarce. Thus, the objective of this work was to evaluate the profile of antimicrobial resistance within Veterinary Medicine. A total of 67 K. pneumoniae isolates from different lesion sites of domestic (39/67) and wild (28/67) animals were confirmed by sequencing the 16S rRNA gene. The highest percentage of K. pneumoniae isolation was from urine isolates with 16% (11/67), lung 13% (09/67) and faeces 12% (08/67). In the susceptibility profile, 11 categories of antibiotics were tested, with the highest resistance to metronidazole being 97% (65/67), ampicillin 94% (63/67), amoxicillin 93% (62/67), sulfonamides 93% (62 / 67), 93% colistin (62/67), and 88% nitrofurantoin (59/67). The ones with the lowest resistance were: meropenem 3% (2/67), imipenem 6% (4/67) and amikacin 16% (11/67). All isolates demonstrated a multidrug resistance phenotype, with 100% (67/67) considered multiresistant bacteria (MDR). The result of this study reinforces that the animals are reservoirs of multiresistant K. pneumoniae.